PENINGKATAN KUALITAS PRODUK “AGAR” RUMPUT LAUT Gracilaria gigas DENGAN PENAMBAHAN IOTA KARAGINAN MELALUI PEMANASAN MODEL “SMOG STEAM - A. Ilalqisny Insan; Dwi Sunu Widyartini (JURNAL LITBANG PROVINSI JAWA TENGAH, 2012)
Gracillaria gigas is one of export commodity seaweed that needs to be developed, because a lot of raw materials utilized for the food industry, medicine, pharmaceuticals, paints and more. Extraction (warming) is done by Steam Smog models, one of which uses steam, because it is more economical and has many advantages in terms of both technology and product. This study aims to know: carrageenan and heating systems Smog Steam models to extract jelly of the Gracillaria gigas. Research carried out for 4 months (March-June 2012), used completely random sampling with a split plot pattern. Main plots were tested directly by the heating of hot water (hot water blanching) and steam (Steam blanching). As a subplot is without the addition of iota carrageenan, 2% of iota carrageenan addition, 3% of iota carrageenan addition and 4% of iota carrageenan addition. Each treatment repeated 3 times. The higher the addition of iota carrageenan, the higher the product that is produced, using either direct heating or hot water vapor. On heating with the addition of 4% iota carrageenan, the highest jelly product is 38.67%, while using steam of heating hot water the highest product that produced is 49.33%, with the best quality jelly based of FAO standards (Quality II)